Peningkatan Literasi Keuangan dan Toleransi Risiko melalui Inklusi Keuangan Menuju Keputusan Investasi dari Perspektif Otoritas Jasa Keuangan - Milzam, Muhammad; Taruna, M. Sigit; Rakhmatika, Devi; Akmalia, Farda; Ayu Regina, Nabila (Universitas Islam Nahdlatul Ulama Jepara, 2024)
The increasing interest of investors, especially among the younger generation, as well as investment instruments with different risks means that investment decisions must be adjusted. This research is aimed at testing and analyzing financial literacy and risk tolerance factors that are bridged by financial inclusion in investment decisions from an economic and juridical perspective based on Financial Services Authority Regulation Number 6 of 2022. The research methodology used for this research is quantitative research by using structural equation model analysis (SEM) with Warp PLS 8.0 software and juridical analysis. The results of data processing show the results on the Financial Literacy variable. Financial literacy has a positive influence on investment decisions. The variables Financial Tolerance and Financial Inclusion have no significant effect on investment decisions. Apart from that, Financial Inclusion in this research shows that it cannot mediate financial literacy and financial tolerance in investment decisions. Then the results of the juridical analysis show that the existence of POJK Number 6/2022 is considered to provide legal certainty in creating favorable conditions for investment activities, with 40 out of 51 respondents agreeing and assessing it as very effective in protecting the public from investment fraud